Temporal complementarity and value of wind-PV hybrid systems across the United States. (December 2022) - Harrison-Atlas, Dylan; Murphy, Caitlin; Schleifer, Anna; Grue, Nicholas
Abstract: Maximizing the utilization of variable renewable energy (VRE) resources will be critical for cost-effective energy transition. Hybrid VRE systems offer potential reliability benefits with stochastic wind and solar. Here, we conduct a comprehensive assessment of temporal complementarity for co-located wind-PV hybrid systems at greater than 1.7 million locations across the contiguous United States. We model hourly variation in potential wind and solar generation for a period spanning 2007–2013 and evaluate robust evidence for complementarity using multiple metrics to assess correlations and stabilization benefits achieved via hybridization. We further explore regional case studies to investigate whether complementarity is an indicator of value, using price taker analysis to quantify the current and expected future value factor for hybrid systems. We find most locations in the U.S. (except for mountainous regions) offer complementarity of hourly wind and PV generation annually with modest seasonal variation. The stability coefficient is a better indicator of value in regions with large variation in wind potential and significant PV penetrations whereas the correlation metrics more clearly indicate value in regions where wind and PV both provide significant shares of generation. Overall, we find broad support for wind-PV hybrid systems to exploit resource synergies with economic benefits. Graphical abstract: Image 1